Hepatoprotective and Antioxidant Potential of Organic and Conventional Grape Juices in Rats Fed a High-Fat Diet - Iselde Buchner; Niara Medeiros; Denise dos Santos Lacerda; Carlos Augusto B. M. Normann; Tanise Gemelli; Paula Rigon; Clovis Milton Duval Wannmacher; João Antônio Pegas Henriques; Caroline Dani; Cláudia Funchal (MDPI AG, 2014)
The objective of this study was to investigate the antioxidant and hepatoprotective effect of the chronic use of conventional (CGJ) or organic (OGJ) grape juice from the Bordeaux variety grape on oxidative stress and cytoarchitecture in the liver of rats supplemented with a high-fat diet (HFD) for three months. The results demonstrated that HFD induced an increase in thiobarbituric acid-reactive substances (TBARS), catalase (CAT) activity and 2',7'-dihydrodichlorofluorescein (DCFH) oxidation and a decrease in sulfhydryl content and superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities. HFD also induced hepatocellular degeneration and steatosis. These alterations were prevented by CGJ and OGJ, where OGJ was more effective. Therefore, it was concluded that HFD induced oxidative stress and liver damage and that the chronic use of grape juice was able to prevent these alterations.